Prevalence of cervical postural alterations in oculomotor disturbances: a Brazilian cohort study - dos Santos, Júlio César Claudino; de Albuquerque-Filho, Luciano Barroso de Albuquerque; Campos, Emille Magalhães Neves; Araújo, Maria Angela Silva Dias de; Fernandes, Maria Goretti; Santos, Marcos André dos; Ribeiro, Maria Amélia Silva de Sousa; Costa, Rafaella Iughetti da; Sampaio-Junior, José Amarilo; Maia, Maria Victoria Rocha Fontenele; Albuquerque, Jullie; Cardoso, Pedro Henrique; et al. (Brazilian Journal of Case Reports, 2023)
The literature suggests that maintaining correct posture depends on a balance between orientation and balance, which is linked to the reflex relationship between the oculomotor system and the superior cervical spine. Any disruption to this relationship can cause postural deviation, as the posture is dependent on head balance and eye horizontality. This study aimed to investigate the prevalence of cervical posture alterations, such as head tilt, rotation, and protrusion, scapular waist changes, scoliosis, kyphosis, and lumbar hyperlordosis, in patients with oculomotor disturbances, including convergent, divergent, and vertical squint, and convergence insufficiency. The study evaluated 24 patients aged between 4 and 39 years old, both male and female, through ocular motility and postural examination. The results showed that all patients with oculomotor disturbances also had postural imbalances, and the percentage of alterations in the posture segments was high. Therefore, oculomotor disturbances can cause postural imbalance, leading to orthopedic and facial asymmetry. The study concluded that patients with oculomotor disturbances should be evaluated to determine the compensatory positions they adopt and set a better visual performance that does not alter their appearance in the long term.